PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN KOMPUTER PADA POKOK BAHASAN JAGAT RAYA MATA PELAJARAN GEOGRAFI - Karisnawati Yuwono; Aunurrahman Aunurrahman; Indri Astuti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe study aimed at producing computer learning media for geography study, the method in this development study using the research and development method and modified with the model design of dick and Carey. The results of the student's performance before and after using the media can be traced to the average score of a student's test of 89.00 ≥75(KKM). In addition to the broad effectiveness of computer study media for geography study, is to be well received, tested, worthy of use and highly effective In learning result by the students in SMA Negeri 1 Belitang Hulu Sekadau. Keywords: Computer Assisted, Development